2016
DOI: 10.1007/s00449-016-1619-4
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly and photocatalytic activity of branched silicatein/silintaphin filaments decorated with silicatein-synthesized TiO2 nanoparticles

Abstract: The fundamental mechanisms of biomineralization and their translation into innovative synthetic approaches have yielded promising perspectives for the fabrication of biomimetic and bioinspired organic-inorganic hybrid materials. In siliceous sponges, the enzyme silicatein catalyzes the polycondensation of molecular precursors to nano-structured SiO2 that is deposited on self-assembled filaments consisting of the two silicatein isoforms (silicatein-α and -β) and the scaffold protein silintaphin-1. Due to its br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Therefore, nano-structured TiO 2 (nanoparticles, nanorods, nanotubes, nanowires, etc.) [12][13][14][15] has received considerable attention in the correlated investigations. Because of the complicated separating procedures, pure nano-structured TiO 2 application was restricted.…”
mentioning
confidence: 99%
“…Therefore, nano-structured TiO 2 (nanoparticles, nanorods, nanotubes, nanowires, etc.) [12][13][14][15] has received considerable attention in the correlated investigations. Because of the complicated separating procedures, pure nano-structured TiO 2 application was restricted.…”
mentioning
confidence: 99%
“…The self-assembly of proteins is an interesting property that is integral to the formation of highly ordered protein architectures. Previous studies examined the self-assembly of silicateins that leads to a structure-guiding property when mixing specified ratios of silicateins such as silicatein-α and silicatein-β to form nanosilica structures and filaments. , Those studies confirmed that the self-assembled silicatein can also catalyze silica polymerization. However, the recombinant silicateins show an aggregation property, which results in the formation of randomly arranged aggregates to form precipitates.…”
Section: Resultsmentioning
confidence: 76%
“…The peptide nanostructures act as scaffold which permit energy transfer and show absorption ability in ultraviolet region, by enhancing their capacity they were used for dye sensitized solar cells [243]. Titanium dioxide can be merged with aggregated protein fibers to produce a template for titanium dioxide photocatalyst [224]. Wang et al fabricated copper phosphate nanosheets in flower shape in which titanium dioxide nanoparticles were integrated over the flower petals which act as photocatalyst for solar light harvesting device [244].…”
Section: Solar Cellsmentioning
confidence: 99%